Histological alterations in placentas of normal and anomalous pups: correlation with neonatal outcomes and fetal health - Lovo, Laura M [UNESP]; Estevam, Marina Vilela [UNESP]; Beretta, Samara [UNESP]; Marmol, Amanda [UNESP]; Pasqui, Loren M [UNESP]; Rodrigues-Silva, Fernanda A [UNESP]; Barreto, Renata O [UNESP]; Hataka, Alessandre [UNESP]; Toniollo, Gilson Hélio [UNESP]; Lourenço, Maria Lúcia G [UNESP]; Apparício, Maricy [UNESP] (Elsevier, 2025)
Given that histological evaluation is a key method for identifying placental alterations potentially linked to congenital and neonatal abnormalities, this study evaluates histological alterations in 89 placentas from pups across three groups: Gelet (elective c-sections with healthy offspring), GDist (therapeutic c-sections with healthy offspring), and GAnom (stillborn offspring or those with fetal abnormalities, regardless of the type of c-section). The placentas were evaluated for the presence of congestion, hemorrhage, inflammatory infiltrate, necrosis, and calcification, and these alterations were graded on a scale: 0 - no alterations, 1 - up to 25 % of the region affected, 2 - up to 50 % affected, and 3 - up to 75 % affected. Histological analysis revealed varying degrees of alterations across groups, with the GAnom group exhibiting the most significant changes. Only 19 % of GAnom placentas were normal, while 81 % displayed notable alterations such as grade 1, 2 and 3 hemorrhage, frequently accompanied by necrosis and inflammatory infiltrates. Statistical analysis showed no significant difference in pup and placenta weights among groups (p > 0.1), but Apgar scores were considerably lower in the GAnom group (p < 0.001). A significant correlation was found between the type of placental alteration and pup health, with anomalous pups showing increased incidences of grade 3 hemorrhage (p < 0.001) and grade 2 necrosis (29 % vs. 6 % in the normal group; p = 0.0002). The presence of necrosis negatively correlated with Apgar scores in normal pups (p = 0.02), indicating its potential impact on neonatal outcomes. These findings highlight the critical association between severe placental alterations and adverse fetal outcomes, emphasizing the need for further investigation into the mechanisms underlying these changes.